Marketing on Consumer Buying Behaviors in Hospitality Industry - Devkota, Jiwan; Shrestha, Jhamka Narayan; Pandit, Shishir; Sharma, Aaditya Shankar (NPRC Journal of Multidisciplinary Research, 2025)
The hospitality industry relies heavily on marketing strategies to influence consumer buying behaviors. Understanding how marketing tactics, including digital marketing and social media influencers, affect consumer decisions is critical for businesses in this sector. This study investigates the role of marketing in shaping consumer behavior in the hospitality industry, focusing on consumer engagement with hotels and restaurants. This research adopts a quantitative approach with a descriptive design. A sample of 132 consumers, aged 18 and above, was selected through convenience sampling from an online survey. The study found that 80.3% of respondents had stayed in a hotel, highlighting the relevance of marketing in their buying decisions. More than 51% agreed that marketing influences their buying behavior, particularly through social media and digital platforms. The majority of respondents found content on digital networking sites interesting and were satisfied with the social media marketing of brands they followed. When asked about the effectiveness of traditional vs. digital marketing, most respondents believed digital marketing was more impactful in the hospitality industry. Marketing plays a significant role in shaping consumer behavior in the hospitality industry. Digital marketing, especially via social media influencers, has a stronger influence compared to traditional marketing methods. This study highlights the importance of leveraging digital platforms and social media to attract and engage consumers in the hospitality sector. Further research can explore the long-term impacts of these marketing strategies on consumer loyalty and business performance.